The mist - Neggers, Carla (Mira Books, 2009)
When Lizzie Rush uncovers evidence that thrill-seeking billionaire Norman Estabrook may be at the center of an international criminal network, she finds herself playing a dangerous game of cat and mouse. When someone sets off a bomb in Boston, Lizzie discovers that Estabrook as well as the FBI director's daughter have disappeared. Together with intelligence officer Will Davenport, Lizzie sets out to track down Estabrook.